Implementation of Indonesia's Defence Policy in Addressing the Implications of the Potential Threat from China's Coastguard Law - Patmi, Sri; Suntanto, Rudy; Suradi, Suradi; Prakoso, Lukman Yudho; Alam, Tasdik Mustika; Mahroza, Jonni; Aliyah, Yurizki; Ilyansyah, Muhammad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
The Chinese government enacted the China Coastguard Law (CCGL) on 1 February 2022, consisting of 8 chapters and 84 articles. Several provisions within this law, particularly Articles 3, 20, 21, 22, 25, and 46-51 pose significant potential for conflict, especially with Indonesia. These articles regulate China’s maritime jurisdiction, the use of weapons, and actions against foreign vessels, which could heighten tensions in the South China Sea. This study aims to analyze Indonesia’s Integrated and Interactive Defence and Security Strategy (IITCA) in response to the threats posed by the CCGL. The research reveals that Indonesia has strengthened multilateral and bilateral defense diplomacy, protected fishermen’s rights, and enhanced its capacity to maintain regional peace and security, in line with the ASEAN Outlook on Indo-Pacific (AOIP). Indonesia has also involved civil society and academia in this integrative strategy. Transparency is maintained through public and international communication, including engagement with organizations such as the United Nations, WTO, ARF, and IMO, as well as cooperation with the fisheries and shipping industries. Control measures are implemented through Confidence-Building Measures (CBM), joint exercises with China and the US, and the reinforcement of maritime security through national and international cooperation. Accountability is ensured by establishing commissions, independent mechanisms, and regular audits and evaluations of defense policies. In addressing the CCGL, Indonesia must strengthen its defense human resources and develop more cohesive maritime policies to manage the escalating conflicts in the South China Sea.